2007
DOI: 10.1124/jpet.106.114124
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Cannabinoid Anandamide Produces δ-9-Tetrahydrocannabinol-Like Discriminative and Neurochemical Effects That Are Enhanced by Inhibition of Fatty Acid Amide Hydrolase but Not by Inhibition of Anandamide Transport

Abstract: Anandamide is an endogenous ligand for brain cannabinoid CB 1 receptors, but its behavioral effects are difficult to measure due to rapid inactivation. Here we used a drug-discrimination procedure to test the hypothesis that anandamide, given i.v. or i.p., would produce discriminative effects like those of ␦-9-tetrahydrocannabinol (THC) in rats when its metabolic inactivation was inhibited. We also used an in vivo microdialysis procedure to investigate the effects of anandamide, given i.v. or i.p., on dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(145 citation statements)
references
References 41 publications
13
130
1
1
Order By: Relevance
“…Rimonabant, however, did not affect the behavior maintained by cocaine when administered alone (140). In agreement with this report, Rimonabant pretreatment did not show any effect on cocaine self-administration under fixedratio schedules of behavior in squirrel monkeys (63), an effect that has been recently replicated and confirmed (141,142). In addition, Rimonabant did not affect the number of cocaine selfinjections in Wistar rats studied under a fixed-ratio 5 schedule of drug delivery (103,104).…”
Section: Effects Of Cannabinoids On Cocaine-maintained Self-administrsupporting
confidence: 78%
See 1 more Smart Citation
“…Rimonabant, however, did not affect the behavior maintained by cocaine when administered alone (140). In agreement with this report, Rimonabant pretreatment did not show any effect on cocaine self-administration under fixedratio schedules of behavior in squirrel monkeys (63), an effect that has been recently replicated and confirmed (141,142). In addition, Rimonabant did not affect the number of cocaine selfinjections in Wistar rats studied under a fixed-ratio 5 schedule of drug delivery (103,104).…”
Section: Effects Of Cannabinoids On Cocaine-maintained Self-administrsupporting
confidence: 78%
“…Anandamide is then metabolized into the cell by an intracellular enzyme, the fatty acid amide hydrolase (FAAH) (60,61), the blockade of which has been shown to prolong the behavioral/neurobiological effects of anandamide (4,61,62,63). In contrast, 2-AG is metabolized through the mono glyceril lipase enzyme (54).…”
Section: Overview On the Brain Endocannabinoid Systemmentioning
confidence: 99%
“…The outcomes of the antagonism tests are reminiscent of previous studies assessing surmountable antagonism of rimonabant by mAEA (Järbe et al 2001); animals ceased responding before full generalization (≥80% drug lever responding) might have been achieved (see also Solinas et al 2007). When agonist dose was held constant, i.e., the mAEA training dose, both rimonabant and AM251 (1 to 3 mg/kg) reduced mAEA (10 mg/ kg) appropriate responding to around 25% or lower, suggesting CB 1 R mediation for the DD effect; this was accompanied by a downward trend in response rate (Järbe et al 2006a).…”
Section: Discussionmentioning
confidence: 88%
“…To account for such findings, it has been suggested that cannabinoid ligands interact with CB 1 R/CB 2 R through different binding motifs and/or through non-CB 1 R/CB 2 R cellular targets including additional cannabinoid subtypes or cannabinoid-like receptors and involvement of vanilloid receptor (VR 1 ) mechanisms (Howlett 2004;Pacher et al 2006;Oz 2006 for reviews). Of these, vanilloid mechanism(s) do not appear important for cannabinoid DD, as the VR 1 antagonist capsazepine did not antagonize the Δ9-THC-like discriminative stimulus effects of anandamide (Solinas et al 2007), nor did the VR 1 agonist O-1839 substitute for DDs maintained by the CB 1 R agonists Δ9-THC and O-1812 (ACEA), a CB 1 R selective anandamide analog ). All of the above postulated mechanisms may, however, affect response rate.…”
Section: Discussionmentioning
confidence: 99%
“…The general procedure and apparatus have been described previously (Solinas et al, 2007). Rats were surgically implanted with a concentric dialysis probe aimed at the shell of the nucleus accumbens (2 mm anterior and 1.1 mm lateral from bregma, 8.0 mm below the dura) (Paxinos and Watson, 2005) under anesthesia.…”
Section: In Vivo Microdialysis In Freely Moving Ratsmentioning
confidence: 99%